Diverse effects of obesity on antitumor immunity and immunotherapy. Issue 2 (February 2023) - Dyck, Lydia; Lynch, Lydia
Abstract: Currently, obesity is one of the biggest health burdens facing society because it causes several comorbidities, such as type 2 diabetes, atherosclerosis, and heart disease. Obesity is also linked to multiple types of cancer. Obesity is the second most common preventable cause of cancer after smoking; the rates of obesity are increasing worldwide, as are the rates of obesity-associated cancer. Multiple factors link obesity to cancer, such as increased levels of growth hormones and adipokines, gut dysbiosis, altered tumor metabolism, and chronic low-grade inflammation. More recently, obesity has been shown to also affect the immune response against cancer. In this review we discuss the interplay between obesity, the immune system, and cancer. Highlights: Increased levels of circulating hormones and cytokines, dysbiosis, low-grade inflammation, and metabolic dysregulation in tumor cells link obesity to cancer development. The suppressive effects of obesity on cytotoxic immune cells, such as natural killer (NK) cells and CD8 T cells, contribute to tumor progression. Nutrient availability and metabolic rewiring in obesity shape antitumor immune responses. In some patient cohorts and cancer types, obese patients [body mass index (BMI) >30] responded better to immune checkpoint blockade than patients with a lower BMI (<30).